A Challenge in Diagnosing Aqueous Misdirection Glaucoma after Keratoplasty - Yunita Sari; Virna Dwi Oktariana (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: The purpose of this case presentation is to report the difficulty of diagnosis and managementof an aqueous misdirection of glaucoma after penetrating keratoplasty (PK).Case Illustration: A 35-year-old male presented to the Glaucoma Division of Cipto MangunkusumoHospital with complain of painfull, redness on the left eye (LE), vomiting, headache. He was reffered fromInfection and Immunology Division with diagnosis of secondary glaucoma after keratoplasty due to cornealulcer and had been treated with glycerin, oral acetazolamide, timolol 0.5% eye drop (ED). The examinationshowed visual acuity of LE at presentation was 1/300 good projection and the intraocular pressure (IOP)was 48 mmHg. Slit lamp examination showed opaque corneal graft, shallow or flat central and peripheralanterior chamber. Iris, pupil, lens and funduscopy were hard to be evaluated. The patient assessed withaqueous misdirection of glaucoma after keratoplasty. Sclerotomy and anterior chamber reformation wasthen performed. One day after surgery, the examination revealed deep anterior chamber and decreased IOPto 24 mmHg, patient received no improvement on visual acuity.Conclusion: The goal addressed in management of aqueous misdirection of glaucoma after keratoplasty arereducing the IOP and preserving optimal graft clarity. However, until recently, there is no consensus aboutthe management of aqueous misdirection of glaucoma after keratoplasty. Scleromotomy with reformation ofan anterior chamber is the alternative treatment when medical therapy fail to control the IOP.